Injury study of the 6-year-old pediatric thorax and abdomen in frontal sled tests using different computational models - Li, Haiyan; Lv, Wenle; Hynčík, Luděk; Zhou, Bingbing; Zhao, Hongqian; Cui, Shihai; He, Lijuan; Ruan, Shijie (Frontiers in Future Transportation, 2022)
The correct use of Child Restraint System (CRS) is an internationally recognized effective measure to protect the safety of child occupants, which can reduce the probability of children's road traffic accident death by 54%-80%. Finite element (FE) study is one of the important methods to study the safety protection of child occupants. This study was aimed to study of 6-year-old (6YO) pediatric thorax and abdomen injuries with different computational models in frontal sled test and the protective effect of CRS on children's occupants. In this study, the verified FE model of 6YO child occupant was placed on the FE model of CRS with a three-point safety belt. In the simulation setup phase, the frontal sled simulation of the 6YO FE model was reconstructed by loading the AAMA pulse. Based on the simulation data of the Q6 dummy FE model and the 6YO child Virthuman model (V6), the frontal sled test simulation of a verified 6YO child FE model with detailed anatomical structure was carried out to pediatric thorax and abdomen injuries under the same experimental conditions in this paper. According to simulation results, the change trends of the injury indexes such as chest acceleration and compression are in good consistency with each other, which can provide effective data for the design of CRS. In addition, the simulation result of the 6YO child FE model with detailed anatomical structure can provide a variety of experimental data, such as the maximum first principal strain value and cloud chart, etc. of the internal organs of the chest and abdomen, providing theoretical basis for the performance analysis and later development of CRS.